Struktur Alur Cerita Pendek Anak â€œBulan Tidak Bohongâ€ Karya Hanifah Nur Fadhilah Menggunakan Pendekatan Objektif - Nandira Putri, Regina (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This study intends to recite and describe the staging of the plot in a short story by Hanifa Nur Fadhilah entitled "Bulan Tidak Bohong" This study discusses children's literature, especially short stories (short stories) and analyzes children's short stories entitled "Bulan Tidak Bohong" by Hanifa Nur Fadhilah. Children's literature has an important role in the development of children's reading interest and imagination. Children's short stories are literary works written with interesting stories and simple language for children. The plot structure in short stories is Introduction to the Situation of the story, Disclosure of Events, Towards the existence of conflict, Peak of conflict, and Resolution. Qualitative methods are used in this analysis, focusing on the intrinsic elements of short stories, namely the plot of the short story. This study intends to recite and describe the staging of the storyline. The purpose of analyzing this plot structure is to build tension, keep the reader's interest, and give direction to the story. By understanding the structure of the plot, readers can follow the development of the story better and feel the emotional changes that occur.